(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Over the recent years ,vitamin C and selenium have been a clear line of defense against the effects of stress.The goal of the study is to indicate the effect of restraint stress in rats on the serum levels of cortisol, the roleof vitamin C and selenium supplement in stress relief by determining their effect on serum cortisol . fortyWistar rats were divided randomly into four equal groups (n=10), all the animal except negative controlexposed to restraint stress for six hours a day . the first group were supplemented with vitamin C in a doseof (50 mg/kg bw/day) orally, the second included given selenium in a dose of (0.02 µg/kg bw/day) orally,the control included ten rats . Blood was collected on 20th days, and serum cortisol were measured byenzyme-linked immunosorbent assay (ELISA). Results showed that supplement of rats with vitamin C hadhigh significant increasein serum cortisol in stressed rat (14.65 ± 5) compared to those with no stress (8.77± 4) which constitute the negative control . The study also revealed that supplement of rats with vitamin C ,Selenium and (vitamin C + Selenium) have highly significantly increased serum cortisol level to be (10.42 ±3.78), (10.29 ± 4.54) and (12.77 ± 3.57) respectively compared to stressed rats . It is concluded that chronicstress restriction can result in cumulative initiation of cortisol secretion in rats. Intake of vitamin C canrelieve stress by increasing decreasing cortisol .